Studies on the electrical and optical conductivity of barium-nickel ferrite nanoparticles doped with Zn - Sadiq H. Khoreem; A. H. AL-Hammadi (Discover Nano)
Abstract The study highlights the significant effects of Zn ions concentration on the optical properties of BaNi2-xZnxFe16O27 ferrites, emphasizing the tunability of the band gap through Zn doping and explores their potential to enhance their optical properties. The barium-nickel ferrite powder, with the composition BaNi2−xZnxFe16O27, was synthesized using the ceramic method. The effects of Zn doping were analyzed using X-ray diffraction (XRD) and UV‒visible (UV–Vis) spectroscopy. XRD confirmed a pure single-phase W-type hexagonal structure, with an increase in both grain size and lattice constant proportional to the Zn content. The optical properties were assessed through UV‒visible spectroscopy, revealing an increaseing of the band gap with increasing Zn concentration, confirming material’s semiconducting behavior.All optical constants, exhibited consistent variation with increasing Zn substitution.. Additionally, both electrical and optical conductivities increased with rising photon energy, while the conductivity peak decreased with higher Zn content. The electric susceptibility was found to decrease as Zn concentration increased. The results indicate that Zn doping leads to significant changes in lattice parameters, crystallite size, and bandgap energy, suggesting potential applications in optoelectronics, photonics devices, and energy storage."